Antibiotic-Resistant Strains of Plague Agent and Development of Procedure for Their Detection by PCR Method - G. A. Eroshenko; G. N. Odinokov; L. V. Anisimova; N. Yu. Shavina; N. A. Vinogradova; V. V. Kutyrev (Проблемы особо опасных инфекций, 2011)
The data of antibiotic-resistant strains of Yersinia pestis isolated from clinical sources and animals are shown in the present study. Highlighted are the reasons of their resistance to different drugs. Represented are two PCRs developed for detection of antibiotic resistance genes, their efficiency has been confirmed using collection of antibiotic-resistant strains of Y. pestis.